Expanding the pH range of glutamate decarboxylase from L. pltarum LC84 by site-directed mutagenesis - Yang, Lijuan; Zhang, Xian; Chen, Jing; Zhang, Yao; Feng, Zhiping (Frontiers in Bioengineering and Biotechnology, 2023)
Glutamate decarboxylase is a class Ⅱ amino acid decarboxylase dependent on pyridoxal-5’-phosphate (PLP), which catalyzes the decarboxylation of substrate L-glutamate (L-Glu) to γ-aminobutyric acid (GABA). Its low enzymatic activity and instability under neutral conditions limit the use of microbial synthesis to produce GABA. In this study, we constructed mutants E313S and Q347H by site-directed mutagenesis, and their specific enzyme activities at pH 4.8 were increased by 62.4% and 12.0% compared with wild type, and also broadened the reaction pH range of LpGAD. The analysis of homology modeling showed that mutant E313S broadened the reaction pH of LpGAD through the influence of surface charge, while mutant Q347H broadened the reaction pH of LpGAD through the stacking effect of aromatic rings. Our results show that mutants E313S and Q347H broaden the reaction pH of this enzyme, making it a good candidate enzyme for practical application in the food industry, laying the foundation for the industrial production of GABA.